2018
DOI: 10.1038/s41467-018-04361-y
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase Phf2 acts as a molecular checkpoint to prevent NAFLD progression during obesity

Abstract: Aberrant histone methylation profile is reported to correlate with the development and progression of NAFLD during obesity. However, the identification of specific epigenetic modifiers involved in this process remains poorly understood. Here, we identify the histone demethylase Plant Homeodomain Finger 2 (Phf2) as a new transcriptional co-activator of the transcription factor Carbohydrate Responsive Element Binding Protein (ChREBP). By specifically erasing H3K9me2 methyl-marks on the promoter of ChREBP-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
77
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 70 publications
3
77
0
Order By: Relevance
“…Our results showed that 97% of PHF2 peaks localized on gene promoters, around the transcription start site (TSS) ( Fig. 1A), as it has been reported in a different cellular context (25).…”
Section: Significancesupporting
confidence: 79%
See 2 more Smart Citations
“…Our results showed that 97% of PHF2 peaks localized on gene promoters, around the transcription start site (TSS) ( Fig. 1A), as it has been reported in a different cellular context (25).…”
Section: Significancesupporting
confidence: 79%
“…S1B). The high overlapping suggests a required H3K4me2/3 mark for effective PHF2 binding at promoters as it is described (13,25). To better understand how PHF2 is targeted to the chromatin, we performed bioinformatics analysis that revealed the most statistically significant predicted PHF2 binding sites using the Homer de novo motif research tool.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the article by Bricambert et al ( 2018 ) fits well into the deepening of the role of Phf2 in metabolic diseases. Specifically, in a mouse model of HF/HSD-induced NAFLD, the authors demonstrated that even by the triggering of diet-induced hepatic steatosis, Phf2 concomitantly reduced lipotoxicity by increasing the production of mono-unsaturated fatty acids (MUFA), thus enhancing the MUFA/saturated fatty acids (SFA) ratio.…”
mentioning
confidence: 77%
“…In this regard, a recent article published in Nature Communication (Bricambert et al, 2018 ) demonstrated that the histone demethylase Plant homeodomain finger 2 (Phf2) protects liver from NAFLD progression. The authors found that an over-expression/induction of Phf2 protected the liver from lipotoxicity and oxidative stress in models of a high-fat/high-sucrose diet (HF/HSD) dependent NAFLD.…”
mentioning
confidence: 99%